(untitled) (ModaPalavra e-periódico, 2023)
This study explored the otherness of things and the sublime (HAN, 2019b) to present the concept of sublime fashion, expanding the conceptualization of authorial fashion. It was based on how sociomateriality manifests itself and constitutes the auretization of the process of creating an authorial fashion brand. The article had a brief discussion about fashion (MCCRACKEN, 2003), notions of materiality from the relational perspective of object orientation (HARMAN, 2018; DELANDA, 2016) and also about alterity and the sublime (HAN, 2019a; 2019b). When detailing the case of Ronaldo Fraga with an interpretative approach, he considered the constitutive elements of the brand and the vision of managers and their consumers, observing the overlaps between creator, object and consumption network. The analyzes show the experiences of materiality’s ravishment, antagonisms and the unusual and disconcerting effects of the sublime for the world and those that return to the creator.